SEROPREVALENCE AND RISK FACTORS OF SURRA INCIDENT IN HORSES AND CATTLES IN EAST SUMBA DISTRICT - Pandjukang, Rambu Peristiwati; Apsari, Ida Ayu pasti; Wardhana, April Hari; Dharmawan, Nyoman Sadra (Buletin Veteriner Udayana, 2024)
Surra caused by Trypanosoma evansi is a disease that appears every year in East Sumba district and causes quite large losses. This study aims to determine the seroprevalence and risk factors that influence the incidence of surra in East Sumba district using a total of 226 horse and cattle blood samples obtained from seven sub-districts and the examination was carried out using the serological method, namely the card agglutination test (CATT/ T. evansi). A semi-structured questionnaire was used to collect data on risk factors associated with surra. The results showed that the seroprevalence of surra in horses and cattle was 32,30%. Seroprevalence in horses was 32,85% and in cattle was 26,31%. The risk factor of presence of flies and maintenance methods statistically have a significant effect on the incidence of surra, while age, gender, the presence of other animals and the farmer's knowledge about surra do not statistically have a significant effect on the incidence of surra. Thus, it is necessary to carry out surra surveillance in cattle which are the reservoirs and preventive measures are needed, especially those related to risk factors wich statistically have a significant effect on the incidence of surra. Apart from that, it is necessary to carry out further research on other risk factors related to the incidence of surra and research in different season periods.